2001
DOI: 10.1210/jc.86.8.3604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GH and/or Sex Steroid Administration on Abdominal Subcutaneous and Visceral Fat in Healthy Aged Women and Men

Abstract: Aging is associated with reduced GH, IGF-I, and sex steroid axis activity and with increased abdominal fat. We employed a randomized, double-masked, placebo-controlled, noncross-over design to study the effects of 6 months of administration of GH alone (20 microg/kg BW), sex hormone alone (hormone replacement therapy in women, testosterone enanthate in men), or GH + sex hormone on total abdominal area, abdominal sc fat, and visceral fat in 110 healthy women (n = 46) and men (n = 64), 65-88 yr old (mean, 72 yr)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
2
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 0 publications
5
84
2
5
Order By: Relevance
“…Furthermore, this finding is consistent with the hypothesis that changes in insulin sensitivity occur before changes in VAF (15). Nevertheless, previous randomised placebo-controlled studies using computer imaging to estimate VAF have generally shown no change in VAF after 6-24 months of testosterone treatment (21,22,23,24). One notable exception is a study of non-obese older men with agerelated hypogonadism, which reported a between-group reduction in VAF that was driven by an increase in the placebo group (70).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, this finding is consistent with the hypothesis that changes in insulin sensitivity occur before changes in VAF (15). Nevertheless, previous randomised placebo-controlled studies using computer imaging to estimate VAF have generally shown no change in VAF after 6-24 months of testosterone treatment (21,22,23,24). One notable exception is a study of non-obese older men with agerelated hypogonadism, which reported a between-group reduction in VAF that was driven by an increase in the placebo group (70).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, testosterone therapy decreases visceral abdominal fat (VAF) (13,14,15) and improves insulin sensitivity (16,17,18,19,20) in some but not in all (21,22,23,24,25,26) studies. Specific characteristics of the populations studied may contribute to these discrepancies.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the effect of testosterone therapy on regional fat distribution, studies on abdominally obese, aging men have been conflicting, probably due to the use of oral preparations of testosterone (6,7,8). Studies that used sufficient testosterone doses reported a significant decrease in subcutaneous fat on the abdomen (SAT), but no change in visceral adipose tissue (VAT) during testosterone therapy (9,10), whereas an old study on middle-aged obese men with higher baseline testosterone levels reported no change in SAT and a decrease in VAT (11). Data on changes in lower extremity fat during testosterone therapy are limited.…”
Section: Introductionmentioning
confidence: 99%
“…In te res san te Da ten er ga ben sich aus der Stu die von Mün zer et al [9] be züg lich des Ziel pa ra me ters vis zera les Fett (Än derung ge mes sen mit tels Kern spin to mo graphie). Ins ge samt wa ren 110 äl te re, ge sunde Men schen im Al ter zwi schen 65 bis 88 Jah re ein ge schlos sen, be han delt wurde mit Wachs tums hor mon 20 µg/kgKG 3-mal pro Wo che für ein hal b es Jahr.…”
Section: Stu DI En Zum Ein Satz In Der Al Ters Me Di Zinunclassified